The Study of Silymarin Release Kinetic in Free and Hydrogel Bound Micellar Forms: Qualitative and Quantitative Analysis Using RPHPLC: The study of silymarin release kinetic - Najafzadeh, Mahsa; Sajjadi, Seyed Mehdi; Zeraatkar Moghaddam, Ali; Fereidouni, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2020)
Silymarin is a safe herbal medicine; however, it has some undesirable properties such as short half-life and poor aqueous solubility. To the best of our knowledge, this study is the first to report utilizing a dual-drug delivery system (DDDS) to enhance the release profile of silymarin from both micelles and hydrogels. In this experimental study, the release profile of micellar silymarin and micelle-hydrogel bounded silymarin during 21 days was examined using Knauer K2600A liquid chromatography. The calibration curve was plotted using the peak-areas of the silymarin at different concentrations.The RP-C18 column allowed a good separation of the components of standard silymarin.LOD and LOQ were 16.5 and 55.02 μg/ml, respectively. The in vitro release profiles of the two compounds showed a rapid release of silymarin, especially in the absence of hydrogel. The cumulative release graph revealed that the hydrogel-bound form has more constant release kinetics than the free micelle form; this means that the hydrogel-bound form may sustain for longer durations.In this study, a dualdrug delivery system based on hydrogel/micelle composites was introduced. The results showed that the Puramatrix hydrogel plays an important role in the constant release of silymarin. Furthermore, the RP-HPLC method presented in this study can be used by other researchers to overcome the difficulties associated with the in vitro separation and quantification of silymarin.